Imperative Sentence Analysis Of The Ministry Of Education's Short Film Series In Teaching Material Recommendation Imperative Sentences Based On Pancasila Learner Profile - Hakim, Titik Dwi Ramthi; Mardliyah, Ummu Zulfa (UPA Bahasa Universitas Tidar And HISKI Kedu, 2024)
Many problems in teaching and learning activities occur due to the ineffectiveness of the media used. Learning media is anything that can be used as an intermediary from the sender (educator) to the recipient (students) so that the learning process occurs. Profil pelajar pancasila supports the independent curriculum program for Pancasila student profiles through its YouTube channel short film series